Exploration of Work Accident Prevention Behavior Among Technical Service Personnel In the Implementation of The 'One Pict Saves You' Movement at PT PLN (Persero) Customer Service Unit Bireuen - Ricky Gunawan; Bobby W. Saputra (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to explore the work accident prevention behaviors of technical service officers in response to the implementation of the "One Pict Saves You" initiative at PT PLN (Persero) Customer Service Unit in Bireuen. This initiative was introduced to improve compliance with the use of personal protective equipment (PPE) as a preventive measure to reduce workplace accidents. The methodology used in this study is a qualitative approach with thematic analysis techniques. Data was obtained through in-depth interviews with supervisors, management, and technical service officers, as well as an analysis of the company's safety documents. Interview questions focused on officers' awareness of the importance of PPE, compliance with safety procedures, and behavioral changes following the implementation of the "One Pict Saves You" initiative. The results indicate that the implementation of this initiative successfully increased awareness and compliance with PPE use. Most officers recognized the importance of PPE in protecting their own safety and felt encouraged by consistent visual monitoring. Additionally, the data demonstrated positive changes in safety behavior, including voluntary compliance and enhanced awareness of safety procedures. However, challenges remain in overcoming factors that inhibit consistent compliance, such as occasional PPE availability issues and ingrained habits. The managerial implications of this research highlight the importance of developing an app-based monitoring system, improving internal communication regarding safety procedures, and providing incentives for officers who comply with safety protocols. The company is advised to continue periodic safety training and awareness programs to ensure that behavioral changes remain sustainable.